(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Heat exchanger is an important device in all the thermal systems. The heat exchanger is wide used instrumentation in several industries like process, petroleum refinement, chemicals, pharmaceutical and paper etc. when learning totally different literature concerning device and double pipe heat exchanger drawback is known on perform and experimental investigation of double pipe device with inner twisted tape sort insert at different mass rate of flow. The system has surveyed different types of flow arrangement and geometric dimension with circular tape to achieve heat transferred in experimental result. The objective of those experiments is Performance analysis of double pipe heat exchanger with twisted tape at totally different mass rate of flow. The experimental set up comprises of double pipe heat exchanger experiment. The equipment includes tube-within-a-tube heat exchangers and twisted tape sort insert with threaded thermocouple junction at every end, a water pump and electric motor. These strategies used to determine the heat transfer rate from the surface and connected temperature of fluid motions additionally used to find the effectiveness.